2021
DOI: 10.1080/21655979.2021.1971031
|View full text |Cite
|
Sign up to set email alerts
|

The circular RNA circ0005654 interacts with specificity protein 1 via microRNA-363 sequestration to promote gastric cancer progression

Abstract: Circular RNAs (circRNAs), a group of unique long noncoding RNAs, are involved in gastric carcinogenesis through multiple mechanisms, including interacting with microRNAs (miRNAs). Here, circ0005654, significantly upregulated in gastric cancer (GC), was chosen for further examination. circ0005654 was analyzed by RT-qPCR. The function of circ0005654 in GC cells was substantiated by loss-of-function assays. The mechanism of circ0005654 on miR-363/specificity protein 1 (sp1) axis was evaluated in GC cells by bioin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Yang et al . ascertained that circ_0005654 promoted specificity protein 1 expression to drive gastric cancer development via miR-363 competition [ 33 ]. Conversely, circ_LARP4 is a potent tumor-inhibitory circRNA in gastric carcinogenesis depending on its ceRNA activity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al . ascertained that circ_0005654 promoted specificity protein 1 expression to drive gastric cancer development via miR-363 competition [ 33 ]. Conversely, circ_LARP4 is a potent tumor-inhibitory circRNA in gastric carcinogenesis depending on its ceRNA activity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the biological role of miRNA-363 in NKTCL progression remains poorly understood although past papers have reported its function in other carcinomas. In previous studies, miR-363 has been confirmed as a tumor-suppressive miRNA that suppresses the growth and metastasis of a variety of malignant tumors, including gastric cancer (11), breast cancer (12), multiple myeloma (13), colorectal cancer (14), and ovarian cancer (15).…”
Section: Original Articlementioning
confidence: 96%
“…Some Wnt pathway-related circRNAs (circ0005654, circ-SFMBT2, circ_SMAD4, circRNA_0044516, and circHIPK3) are markedly upregulated in gastric cancer [73,159,161,195,197]. The expression of circ0005654, circ_SMAD4, circHIPK3, and circheckd1 are positively associated with a poor prognosis in patients with gastric cancer [73,[159][160][161]. Functionally, these circRNAs all contribute to promoting tumor cell proliferation in gastric cancer [73,159,161,194,195,197].…”
Section: Gastric Cancermentioning
confidence: 99%
“…The expression of circ0005654, circ_SMAD4, circHIPK3, and circheckd1 are positively associated with a poor prognosis in patients with gastric cancer [73,[159][160][161]. Functionally, these circRNAs all contribute to promoting tumor cell proliferation in gastric cancer [73,159,161,194,195,197]. Additionally, circ0005654, circRNA_ASAP2, circ-SFMBT2, and circH-IPK3 obviously promote gastric cancer cell migration and invasion.…”
Section: Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation